Influence of Knowledge on Attitude and Practice of Cancer prevention Strategies among Staff in Federal Universities of North-Central Zone, Nigeria - Akorede, Seun Nurudeen (NIU Journal of Humanities, 2020)
The study seeks to: influence of knowledge of cancer prevention strategies on attitude towards cancer prevention strategies, knowledge of cancer prevention strategies on practice of cancer prevention strategies among staff in Federal Universities of North-central Zone, Nigeria. ex-post facto research design was used for the study. The population of the study comprised of 25,361 academic and non-academic staff of the seven Federal Universities in the North-central Zone, Nigeria. A multi stage sampling was used to select 756 respondents. The study found that, knowledge of cancer prevention strategies significantly influence attitude towards cancer prevention strategies (r = 0.838   p=0.0012), knowledge of cancer prevention strategies did not influence practice of cancer prevention strategies (r = 0.071   p=0.2). Based on the findings, it was concluded that; Knowledge of cancer prevention strategies translate into positive attitude towards cancer prevention strategies however, Knowledge of cancer prevention strategies do not mean that staff in Federal Universities of North-central Zone, Nigeria practice cancer prevention strategies. It was therefore recommended that Adequate intervention programmes such as informed radio jingles and health education on improved practice of avoidance of risk factors and health education on positive health behaviours should be carried out by Agencies of government (MDAs), Non-governmental organisations on Academic and Non-academic staff of Universities in North-central Zone to bridge the gap that exist between knowledge, attitude and practice. Keywords: Knowledge, Cancer, Prevention, Strategies, Attitude, Practice